Capabilities of digital servitization: Evidence from the socio-technical systems theory - Münch, Christopher; Marx, Emanuel; Benz, Lukas; Hartmann, Evi; Matzner, Martin (Technological Forecasting and Social Change, 2022)
Driven by pressures for sustainable development and disruptions such as the COVID-19 pandemic, manufacturing companies in the 21st century are affected by two intertwined trends: Industry 4.0 and servitization. Digital servitization, which represents the transition from providing products to offering smart product-service systems, is currently seen as a black box by companies confronting them with major challenges. Current literature has not yet investigated which capabilities are required for the development and provision of smart PSSs. To address this gap, an exploratory multiple case study was performed using semi-structured interviews with 18 representatives of four manufacturing companies and six representatives of companies in a supporting role. A socio-technical systems perspective was adopted to cover the interconnectedness and complementarity of internal and external elements relevant for providing a smart PSS. The study identified 46 capabilities of digital servitization to offer and perform smart PSSs and systemically classified these within the dimensions of the socio-technical systems theory, thus providing companies with numerous insights into successful digital servitization. The results contribute to the practical and academic understanding of digital servitization by outlining capabilities to offer and perform smart PSSs and providing support for the use of socio-technical systems theory to frame these capabilities systematically.
Keywords: Digital servitization; Industry 4.0; Smart product-service system; Smart PSS; Manufacturing

Closing the gap between smart manufacturing applications and data management - Marx, Emanuel; Stierle, Matthias; Weinzierl, Sven; Matzner, Martin (Proceedings of the 15th International Conference on Wirtschaftsinformatik (WI), 2020)
Smart manufacturing refers to the intensified collaboration of machines, products, and people throughout the manufacturing and the supply chain. This facilitates innovative products, services, business models, and processes. Smart manufacturing is premised on emerging technologies such as cloud computing, mobile computing, the Internet of Things, data analytics, and artificial intelligence. A plethora of companies struggles with the implementation of corresponding applications. In research and practice, we see general data management approaches with primary attention on building architectures that are not tailored to fit a particular domain/ application scenario. However, a robust data management concept is vital, as smart manufacturing decisively depends on data. To address this substantial deficit, we conduct a comprehensive literature review, an expert workshop, and semi-structured expert interviews with one of the leading German automotive manufacturers. The result is a catalog of requirements and a framework for data management that fosters the implementation of smart manufacturing applications.<br
Keywords: smart manufacturing; smart factory; data management; data analytics; expert interview

From Services to Smart Services: Can Service Engineering Methods get Smarter as well? - Marx, Emanuel; Pauli, Tobias; Fielt, Erwin; Matzner, Martin (Proceedings of the 15th International Conference on Wirtschaftsinformatik (WI), 2020)
Progress in technologies such as cloud computing or artificial intelligence currently paves the way for services that rely on the exploitation of data. The resulting smart services, however, are only gradually finding their way into practical application. A reason for this delay has been identified in the limited applicability of existing service engineering methods for smart services. In this paper, we identify critical perspectives to address in smart service engineering. Subsequently, we conduct a literature review to identify the extent to which these perspectives are covered by current smart service engineering methods. Our results indicate that even though there is a significant number of smart service engineering methods, some perspectives are rarely considered. We offer practitioners and researchers an overview of the status quo of smart service engineering, thus supporting the former in the selection of methods and pointing out avenues for future research to the latte
Keywords: smart service; service innovation; smart service engineering; service development; systematic literature review

From Suppliers to Complementors: Motivational Factors for Joining Industrial Internet of Things Platform Ecosystems - Marheine, Christian; Pauli, Tobias; Marx, Emanuel; Back, Andrea; Matzner, Martin (Proceedings of the 54th Hawaii International Conference on System Sciences (HICSS), 2021)
Spurred by the internet of things, industry firms are increasingly establishing platforms that animate an ecosystem of external actors to provide complementary offerings. But why do independent firms decide to join these ecosystems and to become complementors? The goal of this study is to disentangle their motivational factors in the context of the industrial internet of things. A theoretical framework is developed a priori based on the knowledge-based view of the firm and complementary logics. The framework is empirically explored using a case study design. Our results indicate that financial, technology, and knowledge gains positively influence the decision of complementors to join the ecosystem. Yet, our interviews reveal relative differences in motivations based on complementors’ uncertainty. Our findings contribute to the research on joining nascent digital platform ecosystems from a complementor perspective and the growing stream of research on industrial internet of things platform
Keywords: Industrial Internet of Things; Platform; Ecosystem

Inhibitors and Enablers of Leverage in Digital Industrial Platform Ecosystems - Pauli, Tobias; Marx, Emanuel; Fielt, Erwin; Marheine, Christian; Matzner, Martin (Business & Information Systems Engineering, 2025)
Digital platforms have demonstrated their disruptive power across various domains, and an increasing number of manufacturing firms have embarked on establishing digital industrial platforms for emerging technologies like the Industrial Internet of Things. Given the technical and organizational complexity of digital industrial platforms, the ways in which complementors can create value by interacting and engaging with them may differ for these platforms. Drawing on a case study conducted at a large multinational platform provider, the article explores how complementors can use digital industrial platforms to their advantage. To this end, the study adopts the concept of leverage, which refers to the ability of platform ecosystems to exert a significant degree of impact that is disproportionate to the input required. The findings indicate that complementors currently primarily benefit from production leverage, utilizing the platform as a technological foundation for individual solutions. However, the utilization of the platform as a marketplace for innovative and generically distributable applications that benefit from innovation and transaction leverage is limited. This is due to a variety of inhibitors, which the platform owner tries to mitigate via enablers through deliberate governance in the form of boundary resources. By unveiling domain-specific manifestations, inhibitors, and enablers across different types of leverage, the study contextualizes leverage within the domain of digital industrial platforms and stresses the need for adopting platform and ecosystem thinking and providing relational governance mechanisms. In addition, it extends the notion of architectural leverage by emphasizing the leveraging ecosystem and its governance through the deliberate orchestration of complementor engagement and underscoring ecosystem leverage based on value co-creation and coordination.
CRIS-Team Scopus Importer:2025-03-07
Keywords: Complementor; Digital industrial platform; Digital platform; Leverage; Manufacturing; Platform ecosystem

Leveraging Industrial IoT Platform Ecosystems: Insights from the Complementors' Perspective - Pauli, Tobias; Marx, Emanuel; Matzner, Martin (Proceedings of the 28th European Conference on Information Systems (ECIS), 2020)
To create value from the increasing amount of data produced by the Industrial Internet of Things (IIoT), many firms establish platforms to collect data and make it available to third parties. Thus, IIoT platforms rely on a diverse ecosystem of complementors for value creation. While platform ecosystems have received considerable attention in research, most studies focus on the platform owner and domains such as video game or mobile platforms. In this article, we conducted a case study to shed light on why complementors choose specific IIoT platforms and how they leverage IIoT platform ecosystems for their benefit. To this end, we collected interview data from 15 firms that provide complementary offerings to an IIoT platform. We identified platform owner relationship, platform owner background, customer decision, platform market position, and platform features as vital criteria for platform choice. Additionally, our findings show that complementors leverage IIoT platforms primarily as a technological basis for individual solutions but not as a marketplace for generic applications. Our study extends research on platform ecosystems by illuminating the complementors’ perspective and adding insights from the IIoT domain. Additionally, our findings provide guidance for platform owners on how to design IIoT platform business models and facilitate leverag
Keywords: Industrial Internet of Things; Platform; Ecosystem; Complementor; Leverage

Modeling Platform Ecosystems - Pauli, Tobias; Marx, Emanuel; Dunzer, Sebastian; Matzner, Martin (ER Forum, Demo and Posters co-located with 39th International Conference on Conceptual Modeling (ER), 2020)
Platforms facilitate the creation of complementary modulesby third parties and act as intermediaries between different groups of ac-tors. Due to the high degree of collaboration between actors, ecosystemsevolve around such platforms. As a result of digitalization, platform busi-ness models are becoming viable in more and more domains. Despite theincreasing variety of different platform ecosystems, means to clearly spec-ify them are scarce. This conceptual ambiguity impedes comparabilityof research and knowledge accumulation. To solve this problem, we pro-pose a domain-specific platform ecosystems modeling language (PEML)which builds on seminal platform ecosystem literature. We demonstratePEML by modeling two real-life platform ecosystems based on onlinecase studies. Our results support researchers and practitioners alike inclearly specifying platform ecosystem
Keywords: Platform·Ecosystem·Domain-Specific Modeling Language

Optimization of production processes using Process Mining - Marx, Emanuel; Matzner, Martin (Netzwerkkongress der ZD.B Initiativen für die Wissenschaft - Abstractband, 2018)

Process Mining for Advanced Service Analytics – From Process Efficiency to Customer Encounter and Experience - Zilker, Sandra; Marx, Emanuel; Stierle, Matthias; Matzner, Martin (Proceedings of the 55th Hawaii International Conference on System Sciences, 2022)
With the ongoing trend of servitization nurtured through digital technologies, the analysis of services as a starting point for improvement is gaining more and more importance. Service analytics has been defined as a concept to analyze the data generated during service execution to create value for providers and customers. To create more useful insights from the data, there is a continuous need for more advanced solutions for service analytics. One promising technology is process mining which has its origins in business process management. Our work provides insights into how process mining is currently used to analyze service processes and how it could be used along the service process. We find that process mining is increasingly applied for the analysis of the providers' internal operations, but more emphasis should be put on analyzing the customer interaction and experienc

Project Management as a B2B Service in the automotive development process - Reiche, Finn; Schmidtner, Markus; Marx, Emanuel; Matzner, Martin; Timinger, Holger (Proceedings of the 17th International Conference on Wirtschaftsinformatik (WI), 2022)
The German automotive industry currently not only faces the effects of COVID-19 on the supply chain but also a disruption by new technologies and new competitors. In order to rise to these challenges, project management must be improved and partners along the supply chain must be integrated more tightly. One part in accomplishing this, is to provide an interorganizational project management service between all involved partners. In order to improve, we first have to understand the current implementation of project management services between the OEM and suppliers and examine what the different actors expect from these services. This working paper addresses this issue by conducting a literature review as well as interviews with project management experts in the automotive industry.<br
Keywords: project management; B2B Services; automotive; digital industrial services

Resilience through supply ecosystems - Challenges in transforming the supply chain into a supply ecosystem as a response to crises and disruptions - Münch, Christopher; Marx, Emanuel; Hartmann, Evi; Matzner, Martin (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2021)

ServML – A Domain-Specific Modeling Language as an Extension of SysML to Model Smart Service Systems - Marx, Emanuel (2022 IEEE 24th Conference on Business Informatics (CBI), 2022)
Modeling smart service systems is a challenging task. Numerous actors with a diverse set of resources form complex systems in which smart products act as boundary objects. In their development, smart service systems combine several disciplines such as service, software, and mechanical engineering with their respective modeling languages and approaches. Despite the increasing importance of smart service systems, there are few practical ways to specify their architecture from both a business and a technical perspective. The lack of conceptual guidance hinders an efficient and meaningful design process in which service and smart product development are isolated. To address this gap, I propose the domain-specific modeling language ServML as an extension of the well-established Systems Modeling Language (SysML) that focuses on complex smart service systems. The application of ServML is demonstrated in a real-world online case. My results support researchers and practitioners alike in designing industrial smart service systems.<br
Keywords: Smart service system; Smart product; Domain-specific modeling language; SysML

Smart Service Systems in Mexico: Implications of the Socio-Economic Context on the Willingness to Co-Create - Marx, Emanuel; Valdés Juárez, Francisco Horacio; Tang, Willi; Matzner, Martin (Proceedings of the 29th European Conference on Information Systems (ECIS), 2021)
IoT generates an enormous amount of data during their operation, which can be analysed and interpreted to discover useful knowledge and ultimately to support or make decisions. Smart service systems constitute networks of multiple actors that co-create value based on this potential of IoT. The intention to adopt IoT is positively related to the willingness of the actors to co-create. As smart service systems are embedded in an overarching social system, the socio-economic context significantly influences this willingness to co-create. In this article, we argue that this systemic perception of value co-creation is an alternative approach to study IT adoption by broadening the focus to all actors involved and to the macro context. We collected interview and secondary data from six firms that offer or participate in IoT applications in Mexico. We identified several factors that motivate and inhibit the company's willingness to co-create. Our study extends research on smart service systems design and provides empirical data of a specific socio-economic contex
Keywords: Smart Service Systems; Iot Adoption; Context; S-D Logic; Case Study.

Supply Ecosystems and The Concept of Resilience - A Literature Review - Münch, Christopher; Marx, Emanuel (Proceedings of the Hamburg International Conference of Logistics, 2022)
Purpose: Established approaches to supply chain management are increasingly being challenged due to disruptive events that neglect the dynamics and interdependencies of supply chains. Supply ecosystems form a new theoretical view of the supply chain that is more in line with systemic thinking, although it is unclear how these can contribute to increased resilience. Methodology: Based on the assumption that supply ecosystems are complex adaptive systems with a dynamic capacity to adapt to changes in an environment and evolve, we conducted a systematic literature review of 24 peer-reviewed journal articles. Findings: The review identifies the attributes of complex adaptive systems making them resilient and matches these with the concept of supply ecosystems. The resulting framework demonstrates how supply ecosystems contribute to increased resilience through the systemic nature. Originality: The paper extends research on supply ecosystems by conceptualizing them as complex adaptive systems and identifying attributes that can contribute to system resilience. Thus, the study contributes to the emerging research of supply ecosystems.
CRIS-Team Scopus Importer:2024-12-16

The Status Quo of Process Mining in the Industrial Sector - Dunzer, Sebastian; Zilker, Sandra; Marx, Emanuel; Grundler, Valentin; Matzner, Martin (Proceedings of the 16th International Conference on Wirtschaftsinformatik (WI), 2021)
Since process mining started to reveal the potential of event logs, it has been applied in various process settings ranging from healthcare to production. Every single setting poses its challenges to process analysts who want to apply process mining. The present paper aims at minimizing such challenges for enterprises in the industrial sector by providing a coherent overview of existing cases. Our systematic literature review relates each production form and layout from existing case studies to the applied process mining type. Further, we use Porter's value chain to distinguish operations from other primary and support activities in production. We present the application of process mining, particularly for the production process and the primary activities other than the operations. The results indicate that process mining fits best with cellular production layouts with batch or line production processes.<br
Keywords: process mining; production; production form; production layout

Transitioning to Platform-based Services and Business Models in a B2B Environment - Matzner, Martin; Pauli, Tobias; Marx, Emanuel; Anke, Jürgen; Poeppelbuss, Jens; Fielt, Erwin; Gregor, Shirley; Sun, Ruonan; Hydle, Katja Maria; Aas, Tor Helge; Aanestad, Margunn; Gordijn, Jaap; et al. (Journal of Service Management Research, 2021)
Given the considerable success of companies such as Apple, Amazon or Airbnb, the term platform is on everyone’s lips today. Accordingly, platforms have long since also found their way into service science. However, mastering the transition from established product-sales-based offerings to platform-based services and business models comes with a multitude of challenges. In a B2B context, incumbent companies need to carefully evaluate how they can benefit from the establishment of platforms, especially in light of the effects on their existing business models and ties to other actors. Hence, we invited scholars with different backgrounds to provide viewpoints on the opportunities and challenges of the transition to platform-based services and business models in a B2B environment. The individual commentaries provide various insights on how to conduct this transition and benefit from it successfully. To do so, they contrast different approaches for establishing and governing ecosystems around platforms, discuss B2B-specific pitfalls and opportunities of platform business models, uncover the supporting role of platforms for smart service development, and stress the importance of platform and ecosystem thinking as a necessary mindse
Keywords: Digital platforms; Business models; Ecosystems; Smart services; Business-to-Business